GLOBAL WARMING: Natural Science versus Social Sciences Issues - Lane, Jan-Erik (European Scientific Journal, ESJ, 2016)
It is true that climate change and its implications are given much more attention now, after the COP21 Agreement in Paris. There are almost weekly conferences about global warming and the debate is intense all over the globe. This is a positive, but one must point out the exclusive focus upon natural science and technological issues, which actually bypasses the thorny problems of international governance and the coordination of states. The social science aspects of global warming policy-making will be pointed out in this article. This is a problematic by itself that reduces the likelihood of successful implementation of the goals of the COP21 Agreement (Goal I, Goal II and Goal III in global decarbonistion).